Validation of a scale to assess the severity of bronchiolitis in a population of hospitalized infants (2013)
Although assessment of the severity of bronchiolitis using severity scores is important both in daily practice and as an outcome measure in clinical trials, many of these scores have not been formally validated or have been only partially validated. We conducted a prospective cohort study on a sample of children diagnosed with bronchiolitis. Two physicians independently assessed all of the children on the modified Wood’s Clinical Asthma Score (M-WCAS) and on the Tal et al. severity score and collected the information required to assess the criterion validity, construct validity, inter-rater agreement, sensitivity to change, and usability of the M-WCAS. The median (interquartilic range [IQR]) of the age of the 54 patients included in the study was 5 (2–9) months. Thirty (55.6%) of the patients were males and 24 (44.4%) were female. The scores of the M-WCAS correlated positively with the scores of the Tal et al. severity score (ρ = 0.761, p < 0.001). The scores of the M-WCAS in patients who required subsequent admission to the PICU were significantly higher than those in patients who required admission only to the pediatric medical floor (PMF) [4.5 (3.6–5.2) vs. 2.5 (1.5–2.5), p < 0.001]. The inter-rater agreement for the raters was found to be κ = 0.897 (p < 0.001), 95% CI (0.699–1.000). The scores of the M-WCAS in patients at admission to the PMF were significantly higher than those obtained immediately before discharge from the hospital [2.5 (1.9–2.5) vs. 1.0 (0.5–1.6), p < 0.001). Our results suggest that the M-WCAS severity score has adequate criterion validity, adequate construct validity, adequate inter-rater agreement, adequate sensitivity to change, and appropriate usability for infants hospitalized for acute bronchiolitis.